Anxiousness in Speaking to Public: Students’ Perspective - Rafidiyah, Dina; Rahmah, Seftiannur; Azizah, Azaria Nur; Adhitama, Muhammad Julian (Eduinfo Media, 2022)
One of important skill that is required for university students to master is public speaking, even more so if they are organization activists. However, mastering speaking through Indonesia and English language requires effort, which made more difficult by their anxiousness. Which is why, the purpose of this study is to research how students from English Education major describe their anxiety as well as overcoming that negative feelings. It is required to research this because public speaking is beneficial after they finished their study and looking for jobs. Narrative Approach will be used to dig deep for nine English Education Department participants’ anxiety and their English usage on front of many people. They relay their anxiety in the past when they were in high school and while these students become organization activists and the method they use to overcome their anxiety to become a better public speaker.